Strategy For Developing Traditional Night Market Pt Safaria Adi Puta - Epi Hasnarella; Hendri Dunan (Cita konsultindo, 2026)
This study examines the development strategies of traditional night markets implemented by PT Safaria Adi Putra, emphasizing the role of leadership and local socio-cultural values in sustaining business performance. A qualitative case study approach was applied, using data collected through observations, in-depth interviews, and documentation. The findings indicate that development strategies include standardization of facilities, structured spatial management, digital promotion, and cultural-based entertainment innovation. Managerial leadership strengthens coordination, trader participation, and stakeholder trust, while socio-cultural values such as mutual cooperation and community bonding enhance market sustainability. The study concludes that the integration of adaptive development strategies, participatory leadership, and socio-cultural values is essential to improving the competitiveness and sustainability of traditional night markets.